Characteristics of composition species of three aquatic insect orders in Phong Dien Nature Reserve, Thua Thien Hue province - Trung, Hoàng Đình; Thuận, Nguyễn Duy (Hue University Journal of Science: Natural Science, 2020)
This paper provides the biodiversity data of the species composition of three aquatic insect orders in Phong Dien Nature Reserve, Thua Thien Hue province. Specimens were collected in seven sites (from upper to lower reaches) of streams from February 2018 to March 2019. The results show a total of 54 species of 37 genera and 18 families, belonging to the following orders: Ephemeroptera, Trichoptera, and Plecoptera. The Ephemeroptera (Mayflies) is the most diversified with 34 species (62.96%), 20 genera (54.05%), and 9 families (50.0%). The second is the Trichoptera (Cadisflies) with 11 species (20.37%), 10 genera (27.03%), and 5 families (27.78%). The third is Plecoptera (Stonflies) with 9 species (16.67%), 7 genera (18.92%), and 4 families (22.22%). The number of collected species decreases with decreasing altitudes. The altitudinal distribution is as follows: 46 species, 31 genera, and 15 families under 500 m; 23 species, 19 genera, and 13 families above 500 m. In addition, the number of species individuals of aquatic insects prevails in lotic water compared with lentic water.